2022
DOI: 10.1002/eco.2430
|View full text |Cite
|
Sign up to set email alerts
|

Dammed water quality—Longitudinal stream responses below beaver ponds in the Umpqua River Basin, Oregon

Abstract: Beaver‐related restoration (BRR) has gained popularity as a means of improving stream ecosystems, but the effects are not fully understood. Studies of dissolved oxygen (DO) and water temperature, key water quality metrics for salmonids, have demonstrated improved conditions in some cases, but warming and decreased DO have been more commonly reported in meta‐analyses. These results point to the contingencies that can influence outcomes from BRR. We examined water quality related to beaver ponds in a diverse coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
0
2
0
1
Order By: Relevance
“…2014, Holthuijzen 2021, Stevenson et al. 2022) dwelling on challenges and opportunities (Abrams et al. 2019), also questioning to ranchers and land managers (Fountain 2014, Charnley 2019, Charnley et al.…”
Section: Resultsmentioning
confidence: 99%
“…2014, Holthuijzen 2021, Stevenson et al. 2022) dwelling on challenges and opportunities (Abrams et al. 2019), also questioning to ranchers and land managers (Fountain 2014, Charnley 2019, Charnley et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, beavers alter the hydrology of river corridors in complex ways that may change the water balance through increased evapotranspiration and impact water quality due to increased stream temperatures and metal release (Briggs et al., 2019; Grudzinski et al., 2022). As a result, studies have found mixed results with respect to groundwater (Bobst et al., 2022; Scamardo & Wohl, 2020) and water quality benefits (Połeć & Grzywna, 2023; Stevenson et al., 2022). Conflicting outcomes, especially with respect to water quality, point to the need to connect the underlying drivers of water quality during inundation and how they scale across different riparian corridors.…”
Section: Discussionmentioning
confidence: 99%
“…Las medidas de adaptación pueden reducir algunos de los efectos del cambio climático sobre los recursos hídricos. Las prácticas de gestión, como la reintroducción del castor americano, han aumentado el almacenamiento de agua en algunos paisajes 142 , y han tenido efectos mixtos en la calidad del agua para el salmón en el Noroeste 143 . Aumentar al máximo las zonas de amortiguación de los bosques ribereños reduce la erosión y la sedimentación, suministra hábitat a la vida silvestre y se proyecta que retrase o reduzca el calentamiento de los arroyos gracias a la mejora de la sombra 144 .…”
Section: Recuadro 73 Efectos Del Cambio Climático En Los Recursos Híd...unclassified